Βιβλιοκρισία:A. Madgearu, Byzantine Military Organisation on the Danube, 10th-12th Centuries (East Central and Eastern Europe in the Middle Ages, 450-1450, v. 22), Brill, Leiden – Boston 2013, σελ. 212, ISBN: 978-90-04-21243-5 - ΚΑΡΔΑΡΑΣ Γιώργος (Byzantina Symmeikta, 2016)
Βιβλιοκρισία: A. Madgearu, Byzantine Military Organisation on the Danube, 10th-12th Centuries (East Central and Eastern Europe in the Middle Ages, 450-1450, v. 22), Brill, Leiden – Boston 2013, σελ. 212, ISBN: 978-90-04-21243-5